2021
DOI: 10.3389/fvets.2021.660565
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Validated Precision Livestock Farming Technologies for Pig Production and Its Potential to Assess Animal Welfare

Abstract: Several precision livestock farming (PLF) technologies, conceived for optimizing farming processes, are developed to detect the physical and behavioral changes of animals continuously and in real-time. The aim of this review was to explore the capacity of existing PLF technologies to contribute to the assessment of pig welfare. In a web search for commercially available PLF for pigs, 83 technologies were identified. A literature search was conducted, following systematic review guidelines (PRISMA), to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 156 publications
0
33
0
2
Order By: Relevance
“…Such system should then ideally be externally validated, and its performance assessed, in order to establish its potential for a wide and useful implementation. Considering the high accuracy (≥ 81.5%) reached by the neural network in our study, we believe that the performance of this system could be similar, or higher, than the performance of existing microphone-based systems, which are aimed at classify stress vocalizations and coughing (> 73% 25 ).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Such system should then ideally be externally validated, and its performance assessed, in order to establish its potential for a wide and useful implementation. Considering the high accuracy (≥ 81.5%) reached by the neural network in our study, we believe that the performance of this system could be similar, or higher, than the performance of existing microphone-based systems, which are aimed at classify stress vocalizations and coughing (> 73% 25 ).…”
Section: Discussionmentioning
confidence: 59%
“…These results suggest that an automated recognition system can be developed for this highly commercial species to allow real-time discrimination of emotional states by valence or context of production. To our knowledge, none of the currently existing monitoring technology (Precision Livestock Farming) developed for pigs can assess the valence of the animals’ emotions 25 . Such a system would thus be highly useful to enable famers to keep track of this important component of animal welfare.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant dataprocessing studies are lacking, although they could help to standardize this process to generate comparable datasets across different studies. The benefit of this work is most essential in light of rapid development in technology in order to manage and improve the welfare of animals within commercial livestock systems [1,2,[30][31][32][33][34][35]. We showed that the data processed by a simple filtering of registrations associated with short durations (<1 min) of stays was suitable for monitoring the number of transitions per individual per zone, accounting for 91% of the actual variance (as observed by video).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that the entire fattening period was not recorded in our study, but only on pre-defined days, it was not possible to evaluate the days prior to a tail biting outbreak retrospectively. Automatic monitoring for reliable behavioural indicators for a forthcoming tail biting outbreak using advanced technology (Precision Livestock Farming) would allow early, preventive interventions [ 63 , 64 ]. The automatic detection of low tail posture as an early warning sign was successfully implemented on a commercial farm using 3D cameras [ 62 ].…”
Section: Discussionmentioning
confidence: 99%